Karakteristik Semen Ayam IPB-D1 - Setiadi, D. R.; Hasibuan, H.; Indriastuti, R.; Arif, A. A.; Rosyada, Z. N. A.; Arifiantini, R. I.; Sumantri, C. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
The aim of this study was to examine semen characteristics of IPB-D1 roosters. A total of 15 IPB-D1 roosters were used in this study, healthy, aged between 6 to 9 months, body weight between 1.2-2.0 kg and placed in individual cages 50 cm × 50 cm × 90 cm. Semen were collected using massage techniques on the back and cloaca rooster. Before collection, cloaca is cleaned using tissue that has been moistened with physiological NaCl solution. The evaluation parameters of semen are macroscopically including volume, color, consistency and pH and microscopic include mass movements, spermatozoa motility (%), spermatozoa morphology (%), concentration and number of spermatozoa per ejaculate. The results showed the semen volume of IPB-D1 was 0.10 ± 0.07 mL, milky white in colour, moderate and dense in concistency and pH 6.97 ± 0.27, Microscopic characteristics of IPB-D1 roosters showed mass spermatozoa movement of 2.73 ± 0.46, spermatozoa motility and concentration were 75.00 ± 6.27% and 3257.50 ± 1303.141×106/mL respectively. It was concluded that IPB-D1 roosters produced good semen quality.